Approximations of McKean–Vlasov Stochastic Differential Equations with Irregular Coefficients - Bao, Jianhai; Huang, Xing (Journal of theoretical probability, 2022)
The goal of this paper is to approximate two kinds of McKean–Vlasov stochastic differential equations (SDEs) with irregular coefficients via weakly interacting particle systems. More precisely, propagation of chaos and convergence rate of Euler–Maruyama scheme associated with the consequent weakly interacting particle systems are investigated for McKean–Vlasov SDEs, where (1) the diffusion terms are Hölder continuous by taking advantage of Yamada–Watanabe’s approximation approach and (2) the drifts are Hölder continuous by freezing distributions followed by invoking Zvonkin’s transformation trick.